2022
DOI: 10.3390/en15020546
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital in Energy Enterprises: Poland’s Case

Abstract: Social capital is currently perceived as one of the basic factors of economic development and economic success of enterprises. However, while there is already much research on social capital in enterprises, there has been little such research in the energy industry. The aim of the publication is to fill the gap in this regard. The basic question that the authors try to answer is whether there is a higher level of capital in energy companies compared to other industries, and if so, what the reasons are for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…Zhang et al, 2018), are likely to advise managers to be more socially responsible and enhance environmental disclosure. Thus, they play a crucial role in formulating an environmental protection vision for the firm (Jędrych et al, 2022; Klimek & Jędrych, 2020) and enhancing its value and reputation.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Zhang et al, 2018), are likely to advise managers to be more socially responsible and enhance environmental disclosure. Thus, they play a crucial role in formulating an environmental protection vision for the firm (Jędrych et al, 2022; Klimek & Jędrych, 2020) and enhancing its value and reputation.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Instead, it denotes their impartial treatment on the balance sheet of a company, akin to other forms of capital that have a substantial influence on the business's sustainability and development. Although human and social capital have been the subject of extensive empirical research and scholarly literature, their practical integration with other facets of business management has been comparatively unexplored [24,25,26,27,28,29,30,31].…”
Section: Sourcesmentioning
confidence: 99%
“…Much of the research on corporate social capital is focused on promoting corporate performance and innovation. Klimek and Jędrych [16] and Jędrych et al [17] found that when the six types of capital, including corporate social capital, are balanced, firms maximize efficiency, while energy firms have higher social capital than firms in other sectors. Fiordelisi et al [18] studied the performance of 1789 companies in 27 countries and found that firms with high social capital outperformed their peers in times of economic hardship.…”
Section: Corporate Social Capitalmentioning
confidence: 99%